2021
DOI: 10.1002/anie.202102538
|View full text |Cite
|
Sign up to set email alerts
|

Organic Tetrabutylammonium Cation Intercalation to Heal Inorganic CsPbI3 Perovskite

Abstract: The in situ formation of reduced dimensional perovskite layer via post‐synthesis ion exchange has been an effective way of passivating organic‐inorganic hybrid perovskites. In contrast, cesium ions in Cs‐based inorganic perovskite with strong ionic binding energy cannot exchange with those well‐known organic cations to form reduced dimensional perovskite. Herein, we demonstrate that tetrabutylammonium (TBA+) cation can intercalate into CsPbI3 to effectively substitute the Cs cation and to form one‐dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 40 publications
7
92
0
Order By: Relevance
“…[24] Steele et al reported that the introduction of substrate clamping and biaxial strain could induce crystal distortions and texture formation within black CsPbI 3 thin films, which were thermodynamically stable after being aged under ambient condition. [25] Besides, cation engineering such as phenylethylammonium (PEA + ), [26] ethylenediamine (EDA + ), [27] tetrabutylammonium (TBA + ), [28] Ca 2+ , [29] Sn 2+ [30] is regarded as an effective way to increase the tolerance factor and reduce the trap state density which can stabilize the black phase and improve the efficiency. We recently found that incorporating a small amount of Br and Cl into CsPbI 3 film (marked as CsPbTh 3 ) exhibited an optimized carrier dynamics performance than pure CsPbI 3 perovskite due to their higher electronegativity and ionization potential than I.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Steele et al reported that the introduction of substrate clamping and biaxial strain could induce crystal distortions and texture formation within black CsPbI 3 thin films, which were thermodynamically stable after being aged under ambient condition. [25] Besides, cation engineering such as phenylethylammonium (PEA + ), [26] ethylenediamine (EDA + ), [27] tetrabutylammonium (TBA + ), [28] Ca 2+ , [29] Sn 2+ [30] is regarded as an effective way to increase the tolerance factor and reduce the trap state density which can stabilize the black phase and improve the efficiency. We recently found that incorporating a small amount of Br and Cl into CsPbI 3 film (marked as CsPbTh 3 ) exhibited an optimized carrier dynamics performance than pure CsPbI 3 perovskite due to their higher electronegativity and ionization potential than I.…”
Section: Introductionmentioning
confidence: 99%
“…Especially when exposed to moisture, the black‐phase CsPbI 3 quickly turns into the yellow‐phase CsPbI 3 (δ‐CsPbI 3 ), which largely limits the cell performance of CsPbI 3 PSCs [3b, 8] . Some strategies have been exploited to stabilize the photoactive black‐phase CsPbI 3 , such as interfacial modification, [4b, 9] additive incorporation, [10] reducing crystal sizes [11] and dimensional engineering [8a, 12] . Interface modification can effectively prevent ambient moisture invasion and simultaneously passivate interface defects; however, bulk defects of CsPbI 3 films still have considerable influence on device performance.…”
Section: Figurementioning
confidence: 99%
“…6l. 104 The experiment showed that tetrabutylammonium (TBA + ) ions can intercalate and repair CsPbI 3 with organic cations through the ion exchange reaction. This cation can intercalate into the PbI 6 4− octahedral structure and exchange the Cs + ; thus the two connected layers fractured and the 3D perovskite structure collapsed and then a 1D TBAPbI 3 protective layer was in situ formed.…”
Section: Strategies For Improving the Efficiency And Stability Of Csp...mentioning
confidence: 99%